A RELATIONS BETWEEN GREEN HUMAN RESORCE MANAGEMENT (GHRM) AND ENVIRONMENTALLY FRIENDLY BEHAVIOR : PERCEPTIONS OF STUDENTS AS PROSPECTIVE EMPLOYEES - Zamzammi, Muhammad Faiq; Utami, Datien Eriska (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study examines the relationship between Green Human Resource Management (GHRM) practices and environmentally friendly behavior among students of Raden Mas Said State Islamic University Surakarta as prospective employees. The study employed a quantitative cross-sectional method, analyzing data from 160 students using Structural Equation Modeling (SEM) with Partial Least Squares. Results indicate that GHRM positively influences both task-related and voluntary green behaviors. Specifically, Green Recrutment and Selections (GRS), Green Performance Management (GPM), and Green Compensation management (GCM) significantly affect task-related behavior, while GRS, Green Training and Development (GTD), GPM, and Green Employee Involement (GEI) impact voluntary behavior. Green psychological climate mediates this relationship, though its indirect effects were weaker than expected. These findings highlight GHRM's role in promoting green behaviors among prospective employees, offering insights for organizations seeking to attract environmentally conscious talent. The study contributes empirical evidence on GHRM's impact from the perspective of future employees. Keywords : Green Human Resource Management ; Employee Green Behavior ; Green Psychology Climate ; Green Recrutmen and Selection ; Green Training and Development ; Green Performance Management ; Green Compensation management ; Green Employee Involement